Tecnologias analíticas e de produção vegetal da aroeira (Myracrodruon urundeuva Allemão) - Lima, João Paulo Pereira de (2018)
Myracrodruon urundeuva Fr. Allemão (Anacardiaceae) is a species of occurrence in the northeastern region of Brazil, popularly known as aroeira-do-sertão, one of the plants whose medicinal use is the most widespread in the region, especially for its ethno-pharmological properties, including antimicrobial activities. According to the documented knowledge on the phytotherapeutic use of aroeira, it was included in the official list of ANVISA Plants, but due to the inadequate extractivism the species was considered in the Official List of Brazilian Flora Species Threatened by Extinction elaborated by the Biodiversitas Foundation under the auspices of the Ministry of the Environment. This work aimed to develop a methodological model to evaluate the integrity of M. urundeuva considering the biological and thermal characterization of the species. The seeds were studied in three different maturation stages I green, intermediate II and mature III, using different analytical methods for their characterization. The material was collected in the municipalities of Sumé and São João do Cariri in the semi-arid region of Paraíba, Brazil. In the biometric characterization the diameter, width and thickness of 100 seeds were determined at each maturation stage using a digital caliper. Seeds in different phases had mean length, respectively, of phase I (4.44 mm), phase II (4.42 mm) and phase III (3.33 mm). In the thermogravimetric characterization, the moisture content was determined by the air circulating greenhouse method in which the samples S1, S2 and S3 presented 74%, 56% and 8.8%, respectively, . for the samples of SJ1 SJ2 and SJ3 presented 69%, 9.3% and 3.4% of the moisture present in the seeds, and the ash content was determined by the methodology 018 / IV Residue by incineration - Ash (IAL, 2005). The samples were analyzed by thermogravimetric (TG) techniques in the heating ratios 5, 10, 20 and 40 ° C.min-1 and differential thermal analysis (DTA) 10°C.min-1. In the TG curves six mass degradation events were observed, both in the inert and oxidative atmosphere, indicating similarity between the profiles, having as results of the activation energy S1, S2 and S3 102,37, 94,41, 94,34 jmol-1 and SJ1, SJ2 and SJ3 97.66, 100.85 and 96.75 mol-1. DTA curves showed two exothermic events in the temperature ranges of 250 ° C to 380 ° C and 420°C to 510°C, and the peak ranging between 312 - 349°C and 449 - 475°C. Pyrolysis coupled to gas chromatography / mass spectrometry (PYR-GC / MS) showed fragments similar to the different stages. For the plant production and monitoring of the development of the shoots, six matrices and 20 buckets per matrix were used, 4 seeds per bucket and 80 seeds per matrix. The results of the M. urundeuva plant production were presented for their germination, development and mortality.